Andrea Mantegna making art (history) - Campbell, Stephen J. (Stephen John) 1963-; Koering, J?er?emie (Art history special issue book series., 2015)
"Explores the Mantegna's potentially transformative impact on the study of the early Renaissance"-- Provided by publisher.